Single port laparoscopic cholecystectomy compared to the standard laparoscopic cholecystectomy - Kumar, Sanjay; Ahmad, Zahir (International Surgery Journal, 2019)
Background: Efforts to improve outcomes of laparoscopic cholecystectomy heralded the advent of single incision laparoscopic cholecystectomy. The objective of this study was to evaluate and compare single port laparoscopic cholecystectomy to the standard laparoscopic cholecystectomy with respect to time required for surgery, postoperative pain, morbidity and complications. Methods: This comparative randomized study was conducted in M.L.B. Medical College, Jhansi among 124 patients. 74 patients were included in the three port laparoscopic cholecystectomy group and 50 in the single port laparoscopic cholecystectomy group. Informed consent was taken. All patients were operated under general anesthesia. Statistical analysis was using independent t-test and chi- square test. Results: The mean operative time was slightly longer in SILC (group I) as compared to CLC/SLC (group II). Postoperative pain on VAS scale in group I after 6 hours (1st day score) was 2.44 in group I and 2.73 in group II (CLC/SLC). But on 2nd day in SILC 1.40 and in CLC/SLC it was 1.81. In SILC (group I) 4 patients out of 50 (8%) developed seroma and 2 patients out of 50 (4%) developed Biliary peritonitis due to the slipped dip. And in SLC/CLC (group II) 3 patients out of 74 (4.05%) developed seroma. Conclusions: SILC can be an effective alternative to traditional CLC/SLC, with the added benefit of minimized scarring and a shorter length of stay. This technique can be performed safely for patients with a multitude of gallbladder diseases without resulting in additional complications.